GRAMMATICAL, DISCOURSE COMPETENCE AND PRODUCTIVE SKILLS AMONG FIRST YEAR ESL LEARNERS - Lavadia, Michael (Issues in Language Studies, 2023)
The study examines the grammatical, discourse, and productive competence of first-year ESL students enrolled in the College of Arts and Sciences at the Carig Campus of Cagayan State University in the second semester of the academic year 2021. It looked specifically at respondent profile factors like sex, parents` highest level of education, the type of high school they graduated from, ethnicity, and media exposure that may help explain differences in the student-respondents’ levels of grammatical and discourse competence, writing and speaking skills. According to the study’s findings, the respondents’ overall grammatical and discourse competence was graded as "average," their overall speaking ability as "competent," and their writing ability as "sufficient to good." Furthermore, a substantial correlation between grammatical and discourse competence and the respondents’ parental education and media exposure was discovered. Speaking skill differences were only accounted by the course, whereas writing skill variants were not explained by any profile variables. The findings also reveal that whereas discourse competence is highly connected with speaking and writing skill, grammatical competence is significantly correlated with writing skill.